2019
DOI: 10.1038/s41597-019-0180-9
|View full text |Cite
|
Sign up to set email alerts
|

FAIR adoption, assessment and challenges at UniProt

Abstract: UniProt continues to support the ongoing process of making scientific data FAIR. Here we contribute to this process with a FAIRness assessment of our UniProtKB dataset followed by a critical reflection on the challenges and future directions of the adoption and validation of the FAIR principles and metrics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 6 publications
(5 reference statements)
0
9
0
Order By: Relevance
“…Important information of spike protein from published papers (Ahmed et al, 2020 ; Lan et al, 2020 ; Ou et al, 2020 ; Rabaan et al, 2020 ; Yan et al, 2020 ) and related databases such as UniProt (Garcia et al, 2019 ) and NCBI were extracted (Yang, 2020 ). Due to the effect of point mutations on the 3D structure, folding, and stability of a protein, it is expected that the immunogenicity of the spike could also be changed.…”
Section: Methodsmentioning
confidence: 99%
“…Important information of spike protein from published papers (Ahmed et al, 2020 ; Lan et al, 2020 ; Ou et al, 2020 ; Rabaan et al, 2020 ; Yan et al, 2020 ) and related databases such as UniProt (Garcia et al, 2019 ) and NCBI were extracted (Yang, 2020 ). Due to the effect of point mutations on the 3D structure, folding, and stability of a protein, it is expected that the immunogenicity of the spike could also be changed.…”
Section: Methodsmentioning
confidence: 99%
“…To further ensure our data is both human-readable and also computationally-tractable and continues to adhere to the FAIR principles ( 2 ), we are working to standardize the representation of all existing UniProt data on the functional impact of human variation. UniProtKB/Swiss-Prot has curated over 81 000 variants in 13,000 human protein sequence records from peer-reviewed literature, annotated with information on the functional impact and clinical significance, when known.…”
Section: Progress and New Developmentsmentioning
confidence: 99%
“…In recognition of the quality of our data, and the service we provide, UniProt was recognised as an ELIXIR Core Data Resource in 2017 ( 1 ) and received the CoreTrustSeal certification in 2020. The data resource fully supports the Findable, Accessible, Interoperable and Reusable (FAIR) data principles ( 2 ), for example by making data available in a number of community recognised formats, such as text, XML and RDF and via Application Programming Interfaces (API)s and File Transfer Protocol (FTP) downloads, providing stable and traceable identifiers for protein sequence and protein sequence features and by fully evidencing our data sources throughout. We have also reviewed and updated our data licencing policies.…”
Section: Introductionmentioning
confidence: 99%
“…FAIR data from Uniprot [23] were combined with Ensembl FAIR data [24] in order to obtain the new datasets used in this study, which were uploaded and univocally identified on Zenodo, the open globally scoped repository (https://about.zenodo.org/principles/ (accessed on 16 February 2021)) under FAIR principle [22]. We described metadata identifying the digital object and the process used to integrate data.…”
Section: Discussionmentioning
confidence: 99%